2005
DOI: 10.1089/neu.2005.22.266
|View full text |Cite
|
Sign up to set email alerts
|

NAAG Peptidase Inhibitor Reduces Acute Neuronal Degeneration and Astrocyte Damage following Lateral Fluid Percussion TBI in Rats

Abstract: Traumatic brain injury (TBI) produces a rapid and excessive elevation in extracellular glutamate associated with excitotoxicity and secondary brain pathology. The peptide neurotransmitter Nacetylaspartylglutamate (NAAG) suppresses glutamate transmission through selective activation of presynaptic Group II metabotropic glutamate receptor subtype 3 (mGluR3). Thus, inhibition of NAAG peptidase activity and the prolong presence of synaptic NAAG were hypothesized to have significant potential for cellular protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 44 publications
10
70
0
Order By: Relevance
“…The increase in righting time, response to toe pinch, seizure rate, mortality and FluoroJade labeling of degenerating neurons in the hilus (4 h study) and CA3 hippocampus (24 h study) of pFPI injured rats compared to the sham group, is consistent with previous work using pFPI systems (Gupta et al, 2012;Zhao et al, 2003;Neuberger et al, 2014;Hallam et al, 2004;Zhong et al, 2005). We also see similar outcomes for injuries from the vcFPI device, which demonstrates that both the devices deliver similar injuries.…”
Section: Induction Of Fluid Percussion Injurysupporting
confidence: 89%
“…The increase in righting time, response to toe pinch, seizure rate, mortality and FluoroJade labeling of degenerating neurons in the hilus (4 h study) and CA3 hippocampus (24 h study) of pFPI injured rats compared to the sham group, is consistent with previous work using pFPI systems (Gupta et al, 2012;Zhao et al, 2003;Neuberger et al, 2014;Hallam et al, 2004;Zhong et al, 2005). We also see similar outcomes for injuries from the vcFPI device, which demonstrates that both the devices deliver similar injuries.…”
Section: Induction Of Fluid Percussion Injurysupporting
confidence: 89%
“…Regional patterns of neuronal degeneration in the hippocampus have been documented following fluid percussion injury in the rat with differing degrees of detail, revealing that the CA2-CA3 fields, hilus, and the DG granule cells are the most vulnerable populations of neurons (Anderson et al, 2005;Hallam et al, 2004;Sato et al, 2001;Zhong et al, 2005). Several studies have reported that post-traumatic hypoxia increased the number of degenerating neurons in the hippocampus (Bramlett et al, 1999b;Clark et al, 1997;Nawashiro et al, 1995), but they did not compare changes in cell death at acute and chronic time points.…”
Section: Immediate Post-traumatic Hypoxia Exacerbated Hippocampal Neumentioning
confidence: 99%
“…Unlike NAA, several biological activities were clearly demonstrated for NAAG either under physiological (58) or pathological conditions (3,37). With regard to head injury, the beneficial effects connected to the inhibition of glutamate carboxypeptidase II, also known as N-acetylated alpha-linked acidic dipeptidase, are of particular interest in models of neuropathies, stroke, and focal TBI (36,59). Glutamate carboxypeptidase II, which catalyzes the hydrolysis of NAAG to glutamate and NAA, is activated under these pathological conditions leading to an increase in glutamate release (3,37,50).…”
Section: Significance Of N-acetylaspartylglutamate Variationsmentioning
confidence: 99%